Wildland Weeds: Paragrass, Urochloa mutica - L. T. Markle; Brent A. Sellers; William A. Overholt (EDIS)
Paragrass (also referred to as Californiagrass) is thought to have been introduced into Florida sometime in the late 1870s as a forage plant. The semiaquatic grass is a native of tropical Africa, and today it is established in both hemispheres in tropical and subtropical regions as a highly palatable fodder. The grass is established in regions of poorly drained soils and along freshwater shorelines in Alabama, Florida, Hawaii, Maryland, Oregon, South Carolina, and Texas. It is an extremely aggressive competitor that can displace many shoreline emergent plants and plants in cultivated or disturbed sites associated with moist soil. Paragrass becomes readily established in wet soils along shorelines where it can form large monocultures. This 4-page fact sheet was written by L. T. Markle, B. A. Sellers, and W. A. Overholt, and published by the UF Department of Agronomy, April 2013.